Strategi Penerapan Kurikulum Integral Berbasis Tauhid (KIBT) dengan Pendekatan Deep Learning dalam Pembentukan Karakter Religius SD Integral Luqman Al- Hakim Mataram - Hani Tazkiyah Mubarokah; Husniati; Radiusman (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study examines the implementation strategy of the Tauhid-Based Integral Curriculum (Kurikulum Integral Berbasis Tauhid/KIBT) using a Deep Learning approach in shaping students’ religious character at SD Integral Luqman Al-Hakim Mataram. The development of religious character faces significant challenges due to the inconsistency between students’ knowledge and the practice of Islamic values in their daily lives. This study employed a qualitative method with a case study approach involving two teacher subjects: lower-grade and upper-grade elementary school teachers. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The findings revealed that the implementation of KIBT through the three principles of Deep Learning—mindful learning, meaningful learning, and joyful learning—was applied to five dimensions of religious character: faith in Allah, honesty, discipline, social awareness, and Qur’an reading skills. In lower grades, the implementation emphasized habit formation through concrete experiences, while in upper grades it focused on internalizing moral awareness through structured reflection, project-based assignments, and the use of digital technology. Supporting factors included a strong tauhid foundation, systematic school programs, a religious school culture, teacher role models, adequate facilities and infrastructure, and school-parent synergy. Meanwhile, the inhibiting factor was the uneven understanding of KIBT and Deep Learning among teachers. This study confirms that the integration of KIBT with Deep Learning creates a holistic educational ecosystem that develops religious character through meaningful, mindful, and enjoyable learning experiences.